Frontiers and future perspectives of neuroimmunology - Qi, Hai; Duan, Shumin; Xu, Yanying; Zhang, Hongliang (Fundamental research (Beijing), 2024)
Neuroimmunology is an interdisciplinary branch of biomedical science that emerges from the intersection of studies on the nervous system and the immune system. The complex interplay between the two systems has long been recognized. Research efforts directed at the underlying functional interface and associated pathophysiology, however, have garnered attention only in recent decades. In this narrative review, we highlight significant advances in research on neuroimmune interplay and modulation. A particular focus is on early- and middle-career neuroimmunologists in China and their achievements in frontier areas of "neuroimmune interface", "neuro-endocrine-immune network and modulation", "neuroimmune interactions in diseases", "meningeal lymphatic and glymphatic systems in health and disease", and "tools and methodologies in neuroimmunology research". Key scientific questions and future directions for potential breakthroughs in neuroimmunology research are proposed.